2005
DOI: 10.1086/429906
|View full text |Cite
|
Sign up to set email alerts
|

Low Colonization Prevalence of Staphylococcus aureus with Reduced Vancomycin Susceptibility among Patients Undergoing Hemodialysis in the San Francisco Bay Area

Abstract: Despite numerous published reports of S. aureus with reduced vancomycin susceptibility, carriage of these isolates remains a rare phenomenon. Given the unclear clinical significance of potential hVISA, it is not clear whether clinical laboratories should identify such strains, or how they should do so.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Therefore, it could not be determined whether higher MICs that were still within the susceptible range were associated with treatment failure. Furthermore, The Antimicrobial Susceptibility Testing subcommittee of 14 Our study did not examine the adequacy of medical and surgical therapy for MRSA infections other than the antibiotic regimen given, removal of catheters in cases of bloodstream infections, and the presence or absence of surgical therapy in bone and joint infections. It is conceivable that other aspects of the medical and surgical treatment could be responsible for a portion of the failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could not be determined whether higher MICs that were still within the susceptible range were associated with treatment failure. Furthermore, The Antimicrobial Susceptibility Testing subcommittee of 14 Our study did not examine the adequacy of medical and surgical therapy for MRSA infections other than the antibiotic regimen given, removal of catheters in cases of bloodstream infections, and the presence or absence of surgical therapy in bone and joint infections. It is conceivable that other aspects of the medical and surgical treatment could be responsible for a portion of the failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen patients (6%) were positive for hVISA. Several research groups have addressed the prevalence of hVISA infections (6,10,11,17), and the frequency of hVISA in these publications is in the range of 0 to 74%. A review that summarized data from several studies (11) reported a prevalence of 1.64%.…”
Section: Discussionmentioning
confidence: 99%
“…[67] These authors have reported that the frequency of heterogeneous VISA in their publications was in the range of 0% to 74%. [6870] Lui et al .,69 analyzed data from several studies and reported a prevalence of 1.64%. In most of these publications, surveillance was not performed routinely, the sample size was small, the studies were retrospective, or the methods for screening and identifying heterogeneous VISA varied among studies.…”
Section: Emergence Of Vancomycin Resistancementioning
confidence: 99%